Characteristics associated with pelvic organ prolapse in women with significant levator ani muscle deficiency. Issue 2 (February 2016) - Rostaminia, Ghazaleh; Peck, Jennifer; Quiroz, Lieschen; Shobeiri, S.
Abstract Introduction and hypothesis Age is a factor associated with symptomatic pelvic organ prolapse (POP) among women with significant levator ani deficiency. Methods This cross-sectional study included patients who were referred for varied pelvic floor disorders, had 3D endovaginal ultrasound as part of their evaluation, and were diagnosed with significant levator ani muscle deficiency defined as a score of 12 or more on 3D endovaginal ultrasound. Patients were categorized as having no pelvic organ prolapse (stages 0 and 1), or symptomatic prolapse (stages 2–4). Results Seventy-six women were available for analysis and found to have significant levator ani muscle deficiency, including 51 with symptomatic POP and 25 without POP. Patients with symptomatic POP were older, (mean age 66 (SD ± 11.8) vs 48 (SD ± 17.3) years;p <0.0001), had greater mean minimal levator hiatus (MLH) area (19.7 cm2 (SD ± 4.6) vs 17.5 cm2 (SD ± 3.5);p  = 0.048), and were more likely to be menopausal (91.3 % vs 54.5 %;p <0.001) compared with those with no POP. In a modified Poisson regression analysis excluding nulliparous women, increasing age (RR = 2.39, 95 % CI 1.03–5.55) and smoking (RR = 1.34, 95 % CI 1.08–1.67) remained associated with symptomatic POP after controlling for one another and the MLH area. Conclusions Among women with significant levator ani deficiency, older women and smokers had an increased prevalence of symptomatic POP. On average, women without POP, but with significant levator ani deficiency were 18 years younger than women with POP and significant muscle deficiency.